Peran Asosiasi Peternak Sapi Indonesia (Aspin) Boyolali Dalam Pemberdayaan Masyarakat(Studi Deskriptif Kualitatif Peran Komunikasi ASPIN dalam Pemberdayaan Kelompok Peternak Sapi di Kecamatan Nogosari, Kabupaten Boyolali) - Kusumawati, Nur Rosita Tri, Drs. Joko Sutarso, M.Si (2017)
In the process of development program, communication is a significant component to create changing that runs to the good way and bring many improvements in social life. The role of communication relates to the way of changing. The paradigm of the development has changed focusing on the social improvement. The process of the improvement of the society needs the roles of the facilitator to dig the local potential in order to increase the wealth of the society. ASPN Boyolali is one of association which covers and develop the cow breeders in Boyolali. As one part of Boyolali, sub district of Nogosari is choosen as a sample to the development of the cow business in Central Java. Using qualitative method, this research aimed to know the role of ASPIN Boyolali in developing the cow breeders in Nogosari so that it can be good example to other cow breeders in Central Java. The data were collected using interview and documentation, then the data were analyzed using interactive analysis of Miles and Huberman. In the data validation, the researcher used source triangulation technique. The result of the study showed the communication role done by ASPIN Boyolali in improving the cow breeders was successful. It can be seen from three aspects: the program of ASPIN Boyolali, the program communication of ASPIN Boyolali, and the success of ASPIN Boyolali. ASPIN Boyolali made interaction to the cow breeder groups using group communication as the medium to socialize its program to the breeders in their regular meeting and also in the training and learning program. The guidance was also conducted by ASPIN Boyolali to give information to the breeders related to its programs. The agents played their role to motivate and educate the breeders so that they could develop their own competences.